Teachers as software development coordinators - Syropoulos, Apostolos; Chiriac, Ilona; Grimalauskas, Irmantas; Sarikaya, Aylin Kirisci; Tatsiou, Eleni; Wachter, Renate (LUMAT-B: International Journal on Math, Science and Technology Education, 2020)
We report the results of an EU-funded project and its impact on participating teachers. Teachers participating in the project had practically no previous knowledge of game-based education whereas they got a thorough understanding of it at the end of the project. In addition, and most importantly, teachers had to guide pupils in designing and implementing computer games. In a way, teachers became software developers, and this is definitely something that strengthens the profiles of the teaching professions. Thus, these EU-funded projects can be beneficial for teachers if teams select interesting projects.